Alkanethiol Monolayer End Groups Affect the Long-Term Operational Stability and Signaling of Electrochemical, Aptamer-Based Sensors in Biological Fluids - Shaver, Alexander; Curtis, Samuel D; Arroyo-Currás, Netzahualcóyotl (ACS applied materials & interfaces, 2020)
Electrochemical aptamer-based (E-AB) sensors achieve highly precise measurements of specific molecular targets in untreated biological fluids. This unique ability, together with their measurement frequency of seconds or faster, has enabled the real-time monitoring of drug pharmacokinetics in live animals with unprecedented temporal resolution. However, one important weakness of E-AB sensors is that their bioelectronic interface degrades upon continuous electrochemical interrogationa process typically seen as a drop in faradaic and an increase in charging currents over time. This progressive degradation limits their in vivo operational life to 12 h at best, a period that is much shorter than the elimination half-life of the vast majority of drugs in humans. Thus, there is a critical need to develop novel E-AB interfaces that resist continuous electrochemical interrogation in biological fluids for prolonged periods. In response, our group is pursuing the development of better packed, more stable self-assembled monolayers (SAMs) to improve the signaling and extend the operational life of in vivo E-AB sensors from hours to days. By invoking hydrophobicity arguments, we have created SAMs that do not desorb from the electrode surface in aqueous physiological solutions and biological fluids. These SAMs, formed from 1-hexanethiol solutions, decrease the voltammetric charging currents of E-AB sensors by 3-fold relative to standard monolayers of 6-mercapto-1-hexanol, increase the total faradaic current, and alter the electron transfer kinetics of the platform. Moreover, the stability of our new SAMs enables uninterrupted, continuous E-AB interrogation for several days in biological fluids, like undiluted serum, at a physiological temperature of 37 °C.